A Study on carbon-neutral parks based on the functions of urban park to solve urban problems - KIM, Taewoo (KDI School, 2023)
The recent increase in global average temperature is causing various global problems such as water scarcity, the risk of starvation, and degradation of biodiversity. It is mainly attributable to the emission of greenhouse gases due to population growth and industrialization. Especially, since 92% of Korea's population is concentrated in cities that account for 17% of the country's land, urban parks are very important not only in solving urban problems, but also in acting as a carbon sink for the cities. According to urban problems, urban parks are classified into landscape improvement and leisure, environmental welfare, environmental pressure reduction, and social function in this study. In order to confirm the carbon absorption capacity of urban parks, the basic unit of carbon emission based on materials was calculated through the review of previous studies and the carbon absorption model depending on the type of trees was applied. Among Sihwa MTV neighborhood parks that are closely related to urban problems, three types of parks that have been completed were selected as target sites. Neighborhood Park No. 46 is a leisure- use park with a land area of 10,789 m2 and a green area ratio of 61%, and various types of facilities have been introduced. Assuming that the life cycle of the neighborhood park is 30 years, it is estimated that the park release about 91.4 tons of carbon. Neighborhood Park No. 63 is an environmental welfare type park with a land area of 10,115 m2 and a green area ratio of 71.4%, and it is estimated that the park emits about 86.5 tons of carbon even though few facilities were introduced. The main part of the park consists of green areas centered on grass, and pines and shrubs with low carbon absorption capacity. Neighborhood Park No. 67 is an environmental welfare type park with a land area of 12,684 m2 and a green area ratio of 85.1% and was estimated to absorb about 46.9 tons of carbon. The park's carbon absorption capacity seems to be due to the introduction of many small-sized trees with high carbon absorption capacity. Through the above case study, I would like to suggest the following as a guideline for carbon neutral parks. Firstly, considering that carbon emissions from the manufacturing process of packaging facilities account for more than half of the park's carbon emissions, the government and ordering departments should encourage the active development and use of Environmental Product Declaration product, and natural materials such as clay and wood with low carbon emission should be used as packaging materials. Secondly, since lawn maintenance has a lot of carbon emissions, it is necessary to avoid introducing a wide area of lawn. finally, medium and small sized trees with high carbon absorption capacity should be planted together, and the planting density should be adjusted for future growth, and active management should be accompanied to prevent dead trees.
Thesis(Master) -- KDI School: Master of Public Management, 2023
Keywords: Carbon dioxide mitigation; Clean energy--Technological innovations